SIMILARITIES AND DIFFERENCES OF GRAMMATICAL CATEGORY CASE IN ENGLISH AND UZBEK LANGUAGES - Shaxizadaeva Aydana Temirbekovna (PEDAGOGS, 2024)
Annotation: This article examines the grammatical category of case in English and Uzbek, highlighting both similarities and differences between the two languages. English language, has largely reduced its case system, primarily retaining it in pronouns, while relying on word order and prepositions for syntactical relationships. In contrast, Uzbek language maintains a rich and productive case system with six main case - nominative, genitive, dative, accusative, locative, and ablative—marked by suffixes on nouns and pronouns.